2019
DOI: 10.1177/1553350619868113
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Versus Laparoscopic Gastrectomy for Gastric Adenocarcinoma: Propensity-Matched Analysis

Abstract: Background. We compared the outcomes of laparoscopic-assisted (LA) and robotic-assisted (RA) gastrectomies performed for gastric adenocarcinoma in the National Cancer Database. Methods. The National Cancer Database was queried for patients 18 years old with stages I to III gastric adenocarcinoma who underwent LA or RA gastrectomy. Propensity matching was performed between the 2 groups with regard to clinical staging, adjuvant treatment, demographics, and the extent of surgery. Results. A cohort of 1893 (1262 =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 23 publications
0
4
1
Order By: Relevance
“…In this study, the 30-day mortality of LG (LG, 0.1%; LDG, 0.0%; LTG, 0.8%), was better than reported in the other large database studies (US National Cancer Database [ 37 ], 2.7%; Japanese NCD [ 11 , 18 , 19 ], 0.2–0.9%); however, it did not differ from RG (RG, 0.2%; RDG, 0.2%; RTG, 0.5%). A similar trend was observed in the estimated blood loss and readmission rate.…”
Section: Discussioncontrasting
confidence: 57%
“…In this study, the 30-day mortality of LG (LG, 0.1%; LDG, 0.0%; LTG, 0.8%), was better than reported in the other large database studies (US National Cancer Database [ 37 ], 2.7%; Japanese NCD [ 11 , 18 , 19 ], 0.2–0.9%); however, it did not differ from RG (RG, 0.2%; RDG, 0.2%; RTG, 0.5%). A similar trend was observed in the estimated blood loss and readmission rate.…”
Section: Discussioncontrasting
confidence: 57%
“…However, the sample size of two meta-analyses was relatively small (6,35), and the study of recurrence-free survival outcome of RG. Compared with their results, our study included some recent studies (27)(28)(29)(30)(31)(32)(33). Noticeably, all the studies are PSM studies, which can minimize selection bias.…”
Section: Discussionmentioning
confidence: 99%
“…Since these specific considerations and the importance to perform an adequate lymphadenectomy to reduce loco-regional recurrence and gastric cancer-related death [ 32 ], the robotic surgical system should be considerate an opportunity to overcome some of the major drawbacks of conventional laparoscopy. After an initial experience [ 11 , 12 ], several authors [ [33] , [34] , [35] , [36] , [37] , [38] , [39] ] demonstrated that robot-assisted laparoscopy gastrectomy is safe and feasible, with reduction in operative blood loss [ 34 ], longer operative time, lesser postoperative morbidity rate [ 16 , 40 ] and no difference in terms of harvested lymph-nodes when compared to laparoscopic and open approach [ 41 ]. The da Vinci system allows surgeon to perform a precise dissection of extra-gastric lymph-nodes, particularly in “difficult” stations such as no.7, 8, 9, 11p and 12a.…”
Section: Discussionmentioning
confidence: 99%